1999
DOI: 10.2337/diacare.22.7.1186
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of advanced glycation end products are associated with left ventricular diastolic function in patients with type 1 diabetes.

Abstract: Increased serum levels of AGEs, unlike serum levels of CML, are associated with heart stiffness in patients with type 1 diabetes, possibly mediated by the cross-linking properties of AGEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(132 citation statements)
references
References 0 publications
8
120
1
Order By: Relevance
“…16 Several investigators have speculated that the mechanism of such 'diabetic cardiomyopathy' might be collagen accumulation, which causes a decrease in myocardial compliance, calcium handling abnormality or a cardiac autonomic neuropathy. [17][18][19] …”
Section: Diabetesmentioning
confidence: 99%
“…16 Several investigators have speculated that the mechanism of such 'diabetic cardiomyopathy' might be collagen accumulation, which causes a decrease in myocardial compliance, calcium handling abnormality or a cardiac autonomic neuropathy. [17][18][19] …”
Section: Diabetesmentioning
confidence: 99%
“…2,[4][5][6] However, previous studies on the association between circulating AGEs and LV structure and function showed mixed results. For example, some studies, [7][8][9] but not all, 10 showed that higher circulating AGEs were associated with impaired diastolic function. Such mixed results were also seen for systolic function.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Experimental studies suggest that increased advanced glycation end-product formation associated with hyperglycaemia may be linked with increased myocardial stiffening and dysfunction. 33,34 Increased myocardial fibrosis presumably contributes to myocardial ischaemia due to the reduction in capillary density and coronary reserve. 32 Recently, even subclinical renal damage has been associated with impaired coronary flow reserve.…”
Section: Discussionmentioning
confidence: 99%